2016
DOI: 10.1016/j.vph.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the mineralocorticoid receptor in glucocorticoid driven vascular calcification

Abstract: Vascular calcification, which is common in the elderly and in patients with atherosclerosis, diabetes and chronic renal disease, increases the risk of cardiovascular morbidity and mortality. It is a complex, active and highly regulated cellular process that resembles physiological bone formation. It has previously been established that pharmacological doses of glucocorticoids facilitate arterial calcification. However, the consequences for vascular calcification of endogenous glucocorticoid elevation have yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Primary aortic VSMCs were isolated from 5‐week‐old mice as described previously . Mice were euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary aortic VSMCs were isolated from 5‐week‐old mice as described previously . Mice were euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Primary aortic VSMCs were isolated from 5-week-old mice as described previously. (3,12,13) Mice were euthanized by cervical dislocation. The aorta was then dissected, the adventitia removed, and the aorta cut open to expose the endothelial layer.…”
Section: Primary Murine Vsmc Isolationmentioning
confidence: 99%
“…Elevated endogenous glucocorticoids were shown to act through mineralocorticoid receptor and facilitate phosphate-induced VSMC calcification [21]. Administration of dexamethasone reduced the expression of MGP, osteopontin and VC-associated factor mRNA on the pericytes, resulting in increased ALP activity and calcium deposition [20].…”
Section: Pericytesmentioning
confidence: 99%
“…11β-HSD1 is a key enzyme that catalyzes the intracellular conversion of the inactive glucocorticoid cortisone to active cortisol (11-dehyrocorticosterone to corticosterone in rodents). Recent studies have suggested that 11β-hydroxysteroid dehydrogenase-1 (11β-HSD1) is an important risk factor for diabetes and diabetic complications [ 4 7 ]. Importantly, it is the activity of 11β-HSD1 that determines the intracellular concentration of active glucocorticoids in the tissues and not the plasma glucocorticoid levels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%